A school-based approach to developing the English proficiency of EAL university students - Muller, Amanda; Arbon, Paul; Gregoric, Carolyn (Journal of Academic Language and Learning, 2015)
This paper provides a case study of a school-based approach to language development and support for English as an additional language (EAL) students within the School of Nursing & Midwifery at Flinders University. The case study addresses the need for greater knowledge about different organisational approaches to EAL support within tertiary education. While there are numerous university-wide and faculty-based programs and support for EAL students, school-based approaches are much less common. The paper outlines the context from which the decision to employ an English for specific purposes (ESP) academic within the school emerged. The initial response and modifications made as a greater understanding of student and staff needs and preferences developed are outlined. Along with the role and activities of the ESP academic, challenges are also discussed.